2011
DOI: 10.1364/oe.19.005817
|View full text |Cite
|
Sign up to set email alerts
|

High angular and spectral selectivity of purple emperor (Lepidoptera: Apatura iris and A ilia) butterfly wings

Abstract: The iridescent features of the butterfly species Apatura iris (Linnaeus, 1758) and A. ilia (Denis & Schiffermüller, 1775) were studied. We recognized the structural color of scales only on the dorsal side of both the fore and hind wings of males of both of the aforementioned butterfly species. The scale dimensions and microstructure were analyzed by a scanning electron microscope (SEM) and transmission electron microscope (TEM). The optical properties were measured and it was found that the peak reflectivity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Nevertheless, the pattern of the surface structure of A. expansa resembles loosely arranged butterfly wings. 15,16 Iridescence is found in A. expansa, as shown in Fig. 3, in which two peaks, 555 nm (green) and 588 nm (yellow), shift as the angle of incidence changes.…”
Section: Resultsmentioning
confidence: 96%
“…Nevertheless, the pattern of the surface structure of A. expansa resembles loosely arranged butterfly wings. 15,16 Iridescence is found in A. expansa, as shown in Fig. 3, in which two peaks, 555 nm (green) and 588 nm (yellow), shift as the angle of incidence changes.…”
Section: Resultsmentioning
confidence: 96%
“…Han et al (2008) reported that the type I scales in the clytie form of Apatura ilia are larger—150 μm long and 60 μm wide. The type I scales are responsible for the violet‐blue iridescence of Apatura ilia (Pantelić et al, 2011). Iridescent violet‐blue can be seen on the whole dorsal wing surface in males and is observed in narrow angular range.…”
Section: Resultsmentioning
confidence: 99%
“…Lamellae on the ridges of the type I scales are dorsally subtriangular, overlap, and form the multilayer structure responsible for iridescence (Fig. 2b; Pantelić et al, 2011). Lamellae exist dorsally on the ridges of the type II scales as well, but these are subcylindrical, slightly widened basally, only partly overlap, and do not produce structural coloration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations